ANALISA VARIASI HARMONIK PASANG SURUT DI PERAIRAN SURABAYA AKIBAT FENOMENA EL-NINO - Sukojo, Bangun Muljo; Witarsih, Diah (Departemen Teknik Geomatika ITS, 2018)
The influence of the El Nino phenomenon can also be studied and analyzed using tidal fluctuation data at sea level. Ups and downs are ups and downs of sea level caused by a combination of gravitational forces from the rotation of the moon, sun and Earth. In addition, changes in atmosphere such as changes in pressure, wind and temperature will affect tidal patterns and tidal activity. The results showed that MSL decrease during El Nino in Surabaya waters followed the linear equation with y = 114.1-0.3782x (R2 = 20,69%) with MSL decrease 4,347 cm during 2014-2015.